Design of Differential Voltage Current Conveyor based operational transconductance amplifier and its application - SHAKTOUR, MAHMOUD (مجلة العلوم الإنسانية والتطبيقية, 2018)
In this paper, implementation a new CMOS of differential voltage current conveyor DVCC based operational transconductance amplifier with a wide linear range. The differential voltage current conveyor is used to realize a multiple input single output filter with band pass and low pass characteristics. PSPICE simulations of the proposed differential voltage current conveyor and its based filter are given using 0.18μm CMOS technology from TMSC MOSIS and dual supply voltages ±0.6V.